1989
DOI: 10.1073/pnas.86.3.1098
|View full text |Cite
|
Sign up to set email alerts
|

Retinal melatonin is metabolized within the eye of xenopus laevis.

Abstract: ABRSTRACTRetinal synthesis of melatonin, a potent modulator of rhythmic retinal processes, is elevated at night as a result of regulation by a circadian clock. Despite high nocturnal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 25 publications
2
72
0
Order By: Relevance
“…Oxidative deamination of 5-MT would lead to the production of 5-methoxytryptophol (5-ML) and/or 5-methoxyindole acetic acid (5-MIAA). This metabolic pathway has been shown to be important in the retina (Cahill and Besharse, 1989) and it should be stressed that the rhythm of 5-MT found in the present study is superimposable upon the rhythm of 5-ML observed by Skene etal. (1987) in the pineal gland of untreated hamsters.…”
Section: Discussionsupporting
confidence: 50%
“…Oxidative deamination of 5-MT would lead to the production of 5-methoxytryptophol (5-ML) and/or 5-methoxyindole acetic acid (5-MIAA). This metabolic pathway has been shown to be important in the retina (Cahill and Besharse, 1989) and it should be stressed that the rhythm of 5-MT found in the present study is superimposable upon the rhythm of 5-ML observed by Skene etal. (1987) in the pineal gland of untreated hamsters.…”
Section: Discussionsupporting
confidence: 50%
“…Melatonin is synthesized on a circadian rhythm with peak levels occurring at night by pinealocytes and ocular tissues (Rohde et al, 1985;Reiter, 1991;Cahill and Besharse, 1992;Martin et al, 1992;Borjigin et al, 1995;Guerlotte et al, 1996;Niki et al, 1998). Although the retinal photoreceptors synthesize melatonin, it is rapidly metabolized in Xenopus retina, so its action is likely restricted to the retina (Cahill and Besharse, 1989). However, the mammalian ciliary body synthesizes melatonin rhythmically and apparently secretes it into the aqueous humor Rohde et al, 1985;Martin et al, 1992).…”
Section: Discussionmentioning
confidence: 98%
“…In numerous non-mammalian and mammalian species, melatonin is rhythmically synthesized in this specialized CNS structure, in both a subpopulation of photoreceptor cells and the retinal pigment epithelium. In some nonmammalian organisms, it is also released to the blood in certain quantities [19,30,35,77,145,153,155]. However, primates and ungulates so-far investigated exhibited high nocturnal expression levels of AA-NAT, but are reported to not form melatonin at substantial rates, because the NASconverting enzyme, hydroxyindole O-methyltransferase (HIOMT) is poorly expressed [13,65,66].…”
Section: Introductionmentioning
confidence: 99%
“…In general, melatonin deacetylating enzymes can be classified as aryl acylamidases (AAAs). Although the conversion of melatonin to 5-MT by these enzymes seems to be important in organisms different from animals, such as dinoflagellates [37,45] and yeast [129], the quantitative significance of this pathway has only become apparent in the retinas of some amphibians, reptiles and fish [19,32,34]. In other retinas in which AA-NAT is strongly expressed, but only small amounts of melatonin are detected, melatonin deacetylation may be considered, too, as long as the low melatonin levels are not attributable to poor Omethylation.…”
Section: Melatonin Deacetylationmentioning
confidence: 99%